Modulatory Effect of Trypanosoma cruzi Infective Stages in Different Dendritic Cell Populations in vitro - Gutierrez, Brenda Celeste; Lammel, Estela; Ramirez, Marcel Ivan; González-Cappa, Stella Maris; Poncini, Carolina Verónica (Frontiers in Cellular and Infection Microbiology, 2020)
Trypanosoma cruzi is a protozoan parasite that infects at least 7 million of persons in the world (OMS, 2019). In the endemic area infection normally occurs by vectorial transmission, however outside normally happens by blood and includes the congenital transmission. The persistence of T. cruzi during the infection suggests the presence of immune evasion mechanisms and the modulation of the anti-parasite response to a profile incapable of eradicating the parasite. Dendritic cells (DCs) are a heterogeneous population of antigen-presenting-cells (APCs) that patrol tissues with a key role mediating the interface between innate and adaptive immune response. Previous results from our lab and other groups have demonstrated that T. cruzi modulates the functional properties of DCs, in vitro and in vivo. During the vectorial transmission metacyclic (m) trypomastigotes (Tp) eliminated along with the insect feces, reach mucous membranes or injured skin. When transmission occurs by the hematic route, the parasite stage involved in the infection is the circulating or blood (b)Tp. Here, we studied in vitro the effect of both infective mTp and bTp in two different population of DCs, bone marrow derived DCs (BMDCs) and XS106, a cell line derived from epidemic DCs. Results demonstrated that the interaction of both Tp imparts different effect in the functionality of these two population of DCs, suggesting that the stage of T. cruzi, route of transmission, portal of entry and DCs maturation status could define the immune response since the beginning of the ingress of the parasite, conditioning the course of the infection.